Analisis Pengelolaan Arsip Dinamis di Instansi A - Fauziah Alfina Adillia; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Politeknik Kampar, 2023)
This research aims to find out how dynamic records are managed, what obstacles are faced in implementing dynamic records management, and how efforts are made to overcome the obstacles faced in implementing dynamic records management at Agency A. This research uses qualitative methods. The data sources in this research are informants, namely the Head of the KUL sub-division, ASN Staff in the KUL section, HR and Legal Staff, and Staff. Data collection techniques in this research used observation, interview, and documentation techniques. Data analysis techniques include data reduction, data display, and conclusion. The results of the research include the creation of archives (receiving and creating archives), recording and filing archives, storing archives, using archives, maintenance (filing, structuring, and storing), and depreciation including the activities of transferring and destroying archives.